Prevalence and Risk Factors for Type 2 Diabetes and Effectiveness of Health Education in Reducing Blood Sugars among Diabetics in Coastal Karnataka-An Intervention Study - Padmanabha, Usha Rani S; Kundapur, Rashmi; Nalam, Udayakiran; Badiger, Sanjeev (National Journal of Community Medicine, 2019)
Introduction: Diabetes contribute to 1.5 million of global deaths with an additional 2.2 million deaths due to uncontrolled blood sugars leading to increased risk for cardiovascular and other disorders. Diabetes is a progressive disease which requires tremendous medical and self-care to prevent acute and long term complications. Lifestyle interventions plays an effective role in maintaining metabolic control. This study was done to assess the prevalence and risk factors for type 2 Diabetes Mellitus and effectiveness of health education as an intervention in reducing blood sugar levels among diabetics in rural population of coastal Karnataka. Methodology: A Community based intervention study done in rural population among subjects aged 18 years and above. Based on the prevalence rate of 10%, a minimum sample size was 160, with 10% as non-respondents, totally 172 subjects were enrolled. Health education as an intervention was done in one among the two villages. Random blood sugars and HbA1c assessment was done before and after intervention. Results: Among the 172 participants, 87 were from Kuthar and 84 belonged to Manjanady village. The overall prevalence of type 2 DM was 29.1%.Middle aged group, obesity, physical inactivity, positive genetic history and hypertension was found to be major risk factors. Health education as an intervention showed significant reduction in mean blood sugars in Kuthar (test arm) post intervention in comparison with Manjanady (control arm). Conclusion: A Community based intervention in the form of health education showed a significant reduction in mean RBS among diabetics of Kuthar village than compared with the controls from Manjanady who received only pharmacotherapy without any lifestyle interventions.